PENGARUH PENYULUHAN MENGGUNAKAN MEDIA VIDEO TENTANG UNMET NEED TERHADAP PENGETAHUAN DAN DUKUNGAN SUAMI - yuni, sriwahyunilubis (Jurnal Kesehatan Ilmiah Aufa Royhan, 2025)
The ever-increasing population is a big problem for countries in the world, especially developing countries. The family planning program is one of the most important national development programs in order to realize a prosperous Indonesian family. The purpose of this study is to determine the influence of counseling using video media about Unmet Need on husbands' knowledge and support in the work area of the Panyabungan Jae Health Center. The type of research used is quasi-experimental research with a pretest-posttest design involving two groups, namely the experimental group and the control group. The population in this study is all husbands of couples of childbearing age who do not have birth control (Unmet Need) in the working area of the Panyabungan Jae Health Center as many as 2095 people, with a sample of 86 people, 43 control groups and 43 experimental groups using the Purposive Sampling technique There is a difference between the knowledge and support of the husband in the control group pretest and posttest with a p value of 0,002, which means there is an effect of counselling using the lecture method about Unmet Need. There was a difference between the knowledge and support of the husband of the pretest and posttest experimental groups with a p value of 0.001, which means that there was an effect of counseling using video media about Unmet Need. It is recommended to health workers to use the results of this research as input for efforts to improve the quality of services to the community, especially those related to Unmet Need.